(untitled) (Web of Teachers: Inderscience Research, 2024)
Glass fibers do not act as an effective reinforcing material when the PP-g-MAH concentration is low. The effect of process parameters on the mechanical properties of composite manufactured specimens is discussed based on the results of tensile tests, three-point flexural tests, Izod impact tests, heat distortion temperature and melt index.